2022
DOI: 10.3390/polym14173541
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Oligomer Chitosan/Polyvinylpyrrolidone Coating for Enhancing Antibacterial, Hemostatic Effects and Biocompatibility of Nanofibrous Wound Dressing

Abstract: A synergistic multilayer membrane design is necessary to satisfy a multitude of requirements of an ideal wound dressing. In this study, trilayer dressings with asymmetric wettability, composed of electrospun polycaprolactone (PCL) base membranes coated with oligomer chitosan (COS) in various concentrations of polyvinylpyrrolidone (PVP), are fabricated for wound dressing application. The membranes are expected to synergize the hygroscopic, antibacterial, hemostatic, and biocompatible properties of PCL and COS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The study also emphasized the potential of natural polymers like chitosan in promoting wound healing [ 241 ]. The study investigated the wound healing effects of ENS Mh (manuka honey) 15%@PVP mats compared to a traditional wound dressing on mice with circular wounds on their dorsal back [ 242 ]. The advanced dressing with ENS Mh@PVP showed great results in wound healing.…”
Section: In-vivo Studiesmentioning
confidence: 99%
“…The study also emphasized the potential of natural polymers like chitosan in promoting wound healing [ 241 ]. The study investigated the wound healing effects of ENS Mh (manuka honey) 15%@PVP mats compared to a traditional wound dressing on mice with circular wounds on their dorsal back [ 242 ]. The advanced dressing with ENS Mh@PVP showed great results in wound healing.…”
Section: In-vivo Studiesmentioning
confidence: 99%
“…Doan and colleagues reported that 95% of the wound area healed after 10 days post-treatment with the multilayer membrane [ 111 ]. The newly grown skin shared a resemblance with the native tissue and illustrated the progressive construction of vascular systems, hair follicles, etc.…”
Section: Skinmentioning
confidence: 99%
“…Chitosan-based membranes and scaffolds are known for their antibacterial properties. A multilayer membrane for facilitating wound healing, which consists of oligomer chitosan, polycaprolactone, and polyvinylpyrrolidone, was assembled by Doan and colleagues [ 111 ]. According to the results, the composite membrane was able to inhibit the growth of several bacteria types.…”
Section: Skinmentioning
confidence: 99%
“…As a non-ionic polymer, PVP exhibits unique physical and chemical features such as low toxicity, solubility in both water and organic solvents, acid and alkali resistance, oxidation resistance, and stabilizing effect on colloids. [14][15][16] PVP can be used as a colloidal stabilizer, surfactant, dispersant, and even reducing agent. 17 Wang et al used PVP as dispersant in the preparation of AgNPs.…”
mentioning
confidence: 99%